Teacher Survival in a Web-based Constructivist Learning Environment: A Malaysian Experience - Kaur, Abtar; Kaur, Kuldip, Assoc Prof Dr (2001)
Educators are well aware of teacher support as a form of scaffold that helps learners reach their “zone of proximal development” (Vygotsky, 1978). An online case study conducted over 4 weeks in an elementary school in Malaysia showed that teacher support came in six multiple forms. However, the nature of an online constructivist learning environment presents a difficult task for the lone teacher in supporting all students reach their desired learning level. This paper will discuss the need for intelligent agent technology to support the teacher reach his/her ‘zone of proximal support’.